A handbook for institutional academic and program planning: from idea to implementation - Kieft, Raymond N.; Armijo, Frank; Bucklew, Neil S. (Colorado, EUA : NCHEMS, 1978)
Fotocopia y engargolado
Keywords: Educación superior; Universidades y colegios